Reformulation of Political Party Support Requirements for Presidential Candidacy in Realizing an Aristocratic State in Indonesia - Nana Supriana; Dini Dewi Heniarti (Jurnal Daulat Hukum, 2026)
This research aims to analyze the urgency of reformulating political party support requirements for presidential candidacy to mitigate oligarchic dominance in Indonesia while realizing a modern aristocratic state. The study employs a normative juridical approach integrated with a socio-legal approach, utilizing a descriptive-analytical research specification. Secondary data, including the 1945 Constitution, Law No. 7 of 2017, and recent Constitutional Court decisions, were analyzed qualitatively through document studies and international institutional comparisons. The findings indicate that the current quantitative presidential threshold has fostered political cartelization and restricted the emergence of competent alternative leaders by prioritizing financial capital over statesmanship. As a primary conclusion, this study offers novelty by proposing the Merit-Based Party Endorsement System (MBPES) as an alternative institutional design. This model reinterprets the concept of modern aristocracy not as hereditary rule, but as governance by individuals possessing superior moral and intellectual virtues. The research's novelty lies in shifting the nomination criteria from mere parliamentary seat counts to qualitative indicators, including internal party meritocracy, deliberative public scrutiny, and an independent epistemic filter. This reformulation is vital to fill the normative vacuum following Constitutional Court Decision No. 62/PUU-XXII/2024, ensuring that presidential candidates are selected based on objective ethical integrity and leadership capacity. Ultimately, this approach is expected to restore constitutional dignity and align the electoral process with the principles of substantive Pancasila democracy in Indonesia.